DETERMINAN FAKTOR PEMANFAATAN APLIKASI SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) DENGAN METODE HUMAN ORGANIZATION TECHNOLOGY (HOT-FIT) DIRUMAH SAKIT UMUM SEMBIRING DELI TUA TAHUN 2024 - br sinulingga, Emmenita carina (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2025)
Hospital Management Information System (SIMRS) is an IT-based application designed to manage the entire hospital service and administration process in an integrated manner to increase efficiency and effectiveness. A hospital is a health service facility that provides comprehensive medical services, including RI, RJ, and emergency and as a place for research in the health sector. HOT-Fit is an information system evaluation model that assesses the suitability between human, organizational, technology, and Net-Benefit aspects in supporting the successful use of the system. This study aims to analyze the determinants of factors for the use of the Hospital Management Information System Application (SIMRS) using the Human Organization Technology-Fit (HOT-FIT) method at Sembiring General Hospital. This study uses a quantitative design with a cross-sectional approach involving SIMRS users, namely 80 respondents into a sample selected through the proportionate stratified random sampling technique. Data analysis used Univariate and Bivariate (Pearson Product Moment Correlation). The results showed that all independent variables had a significant relationship with the use of SIMRS at RSU Sembiring (P-Value<0.05). The variables of System Quality, Service Quality, System Users, and Organizational Structure P-Value (0.001, 0.001, 0.005, 0.004) with r are in the range of 0.20-0.399 (Weak). Meanwhile, the Information Quality Variable, user satisfaction and environmental conditions of the facility P-Value (0.001, 0.001, 0.001) with r are in the range of 0.40-0.599 (Quite Strong) This means that these three factors play an important role in increasing the effectiveness of using SIMRS. These findings show that the success of SIMRS implementation is largely determined by human, technological, and organizational aspects. Therefore, hospitals are advised to continue to improve the quality of systems, services, and user training to optimize the overall utilization of SIMRS